Safety and audiological outcome in a case series of tertiary therapy of sudden hearing loss with a biodegradable drug delivery implant for controlled release of dexamethasone to the inner ear - Plontke, Stefan K.; Liebau, Arne; Lehner, Eric; Bethmann, Daniel; Mäder, Karsten; Rahne, Torsten (Frontiers in Neuroscience, 2022)
Background: Intratympanic injections of glucocorticoids have become increasingly common in the treatment of idiopathic sudden sensorineural hearing loss (ISSHL). However, due to their fast elimination, sustained applications have been suggested for local drug delivery to the inner ear. Methods: The study is based on a retrospective chart review of patients treated for ISSHL at a single tertiary (university) referral center. We included patients who were treated with a solid, biodegradable, poly(D,L-lactic-co-glycolic acid) (PLGA)-based drug delivery system providing sustained delivery of dexamethasone extracochlear into the round window niche (n=15) or intracochlear into scala tympani (n=2) for tertiary therapy of ISSHL in patients with non-serviceable hearing after failure of primary systemic and secondary intratympanic glucocorticoid therapy. We evaluated the feasibility and safety through clinical evaluation, histological examination, and functional tests (pure-tone threshold [PTA], word recognition scores [WRS]). Results: With adequate surgical preparation of the round window niche, implantation was feasible in all patients. Histologic examination of the material in the round window niche showed signs of resorption without relevant inflammation or foreign body reaction. In patients where the basal part of scala tympani was assessable during later cochlear implantation, no pathological findings were found. In the patients with extracochlear application, average preoperative PTA was 84.7 dB HL (SD: 20.0) and 76.7 dB HL (SD: 16.7) at follow-up (p=0.08). The preoperative average maximum WRS was 14.6% (SD: 17.9) and 39.3% (SD: 30.7) at follow-up (p=0.11). Six patients (40%), however, reached serviceable hearing. The two patients with intracochlear application did not improve. Conclusion: The extracochlear application of the controlled release system in the round window niche and - based on limited observations - intracochlear implantation into scala tympani appears feasible and safe. Due to the uncontrolled study design, conclusions about the efficacy of the treatment are limited. These observations, however, may encourage the initiation of prospective controlled studies using biodegradable controlled release implants as drug delivery systems for the treatment of inner ear diseases.